Infected congenital pericardial cyst with mass effect on adjacent structures, a rare presentation in an infant in LMIC setting: a case report and review of literature - Ashagre Gebremichael Ganta; Wintana Tesfaye Desta (BMC Pediatrics)
Abstract Background Giant pericardial cysts are rare mediastinal lesions that can lead to significant morbidity if complicated by infection, compression of adjacent structures, or secondary complications such as right-sided heart failure. This case report highlights the diagnostic and therapeutic challenges of managing an infected giant pericardial cyst in a resource-limited setting in Africa. Case presentation A 2 months old infant presented with symptoms of fast breathing, dyspnea, fever, and signs of right-sided heart failure, including peripheral edema and ascites. Imaging studies, including chest X-ray and computed tomography (CT), revealed a large cystic mass in the pericardial region compressing the right heart chambers. Emergency Surgical excision was performed, and histopathological analysis confirmed the diagnosis of an infected pericardial cyst. Postoperatively, the patient recovered well, with resolution of symptoms, including signs of right-sided heart failure, and no recurrence at follow-up. Conclusion This case underscores the importance of considering pericardial cysts in the differential diagnosis of mediastinal masses, particularly in the presence of infectious symptoms or cardiac compression leading to right-sided heart failure. It also demonstrates the feasibility of successful management through timely surgical intervention, even in resource-limited settings. This report contributes to the sparse literature on infected pericardial cysts and provides valuable insights into their management in low-resource environments. Clinical trial number Not applicable.